Renewable Energy Communities: Optimal sizing and distribution grid impact of photo-voltaics and battery storage. (1st November 2021) - Weckesser, Tilman; Dominković, Dominik Franjo; Blomgren, Emma M.V.; Schledorn, Amos; Madsen, Henrik
Abstract: In this paper, an extensive study of Renewable Energy Communities and their potential impact on the electric distribution grid has been carried out. For that purpose, a Linear Programming optimization model sizing the energy community's Photo-Voltaic and Battery Energy Storage System was developed. The linear programming model was soft coupled with power flow analysis to investigate the impact of different energy community configurations on distribution grids. Different distribution grids (city, suburban, village), different energy community configuration, different operating strategies and different battery placements were investigated. The results showed that when the battery is located at the beginning of the feeder, then the energy community does not impact the observed minimum and maximum voltage. Moreover, it was found that depending on the energy community's operating strategy the low-voltage grid loading can be reduced by up to 58 %. The energy community's sizing showed that optimal capacities of photo-voltaics and communal batteries were up to three times larger for the case of city grid, following the operating strategy of maximizing the energy community's own economic benefit than in other operating strategies and grid types. Highlights: An extensive study of Renewable Energy Communities (ECs) & their impact on the grid. An optimization model for sizing PV&BESS considering different operation strategies. Grid impact analysis for different distribution grid types and EC configurations. Identification of crucial EC properties, which determine its impact on the grid.